2003
DOI: 10.1002/cncr.11810
|View full text |Cite
|
Sign up to set email alerts
|

Sequential interleukin 3 and granulocyte‐macrophage–colony stimulating factor therapy in patients with bone marrow failure with long‐term follow‐up of responses

Abstract: BACKGROUNDInterleukin‐3 (IL‐3) and granulocyte‐macrophage–colony stimulating factor (GM‐CSF) have synergistic, hematopoietic growth‐promoting activity in preclinical studies. Because of the paucity of effective therapies for patients with chronic bone marrow failure states, the authors studied the biologic activity of sequential IL‐3/GM‐CSF in such patients.METHODSIL‐3 was given subcutaneously for 5 days (at escalating doses of 0.15 μg/kg, 0.3 μg/kg, 0.6 μg/kg, 1.2 μg/kg, 2.5 μg/kg, 5.0 μg/kg, 10.0 μg/kg, or 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…This may suggest that repetitive administrations and/or higher doses of GM-CSF could have a more pronounced beneficial effect. We chose the 2 g of GM-CSF (8 -10 g/kg) dose because it is close to the subcutaneous doses (5 g/kg) used in humans for agranulocytosis (27)(28) and to intraperitoneal doses used to study hormonal GM-CSF effects in rodents (29). After daily administrations of such doses, adverse effects such as fever, myalgia, malaise, or rash occur in 20 -30% of patients but remain moderate (30), whereas higher doses are often associated with severe adverse effects (30).…”
Section: Experimental Protocol and Behavioral Resultsmentioning
confidence: 99%
“…This may suggest that repetitive administrations and/or higher doses of GM-CSF could have a more pronounced beneficial effect. We chose the 2 g of GM-CSF (8 -10 g/kg) dose because it is close to the subcutaneous doses (5 g/kg) used in humans for agranulocytosis (27)(28) and to intraperitoneal doses used to study hormonal GM-CSF effects in rodents (29). After daily administrations of such doses, adverse effects such as fever, myalgia, malaise, or rash occur in 20 -30% of patients but remain moderate (30), whereas higher doses are often associated with severe adverse effects (30).…”
Section: Experimental Protocol and Behavioral Resultsmentioning
confidence: 99%
“…54 In 2 additional studies, active bleeding was reported in 18% to 23% of all patients at baseline, irrespective of platelet count. 55,56 In studies of a variety of treatments for MDS, rates of moderate-to-severe hemorrhage of 18%, 57 gastrointestinal hemorrhage of 6% to 7%, 58,59 and intracranial hemorrhage of 3% to 5% 42,60 have been observed. In patients with AML and MDS who were receiving combination salvage chemotherapy, 15% of patients had a mild-to-moderate hemorrhage, and 4% of patients had a severe hemorrhage.…”
Section: Clinical Consequences Of Thrombocytopeniamentioning
confidence: 99%
“…95,96 Growth factors nonspecific of the platelet lineage, including interleukin (IL)3, IL6, and IL11, have been used with some success, but they also produce side effects. 95,97,98 In exceptional cases, a peripheral mechanism of platelet destruction may predominate in MDS, as evidenced by platelet lifespan studies, with a possible success of splenectomy in our experience. 99 Because TPO itself is immunogenic, leading to thrombocytopenia, TPO receptor agonists including romiplostim and eltrombopag have been designed to treat thrombocytopenias of different origins.…”
Section: Treatment Of Neutropenia and Thrombocytopeniamentioning
confidence: 61%